The law of innocence [compact disc, unabridged] - Connelly, Michael, 1956- (Connelly, Michael, 1956- Lincoln lawyer novel (Hachette Audio (Firm)), 2020)
Defense attorney Mickey Haller is pulled over by police, who find the body of a client in the trunk of his Lincoln. Mickey knows he's been framed. Now, he has to figure out who has plotted to destroy his life and why.